2023
DOI: 10.3389/fimmu.2022.1016214
|View full text |Cite
|
Sign up to set email alerts
|

Duck TRIM29 negatively regulates type I IFN production by targeting MAVS

Abstract: The innate immune response is a host defense mechanism that induces type I interferon and proinflammatory cytokines. Tripartite motif (TRIM) family proteins have recently emerged as pivotal regulators of type I interferon production in mammals. Here, we first identified duck TRIM29, which encodes 571 amino acids and shows high sequence homology with other bird TRIM29 proteins. DuTRIM29 inhibited IFN-β and IRF7 promoter activation in a dose-dependent manner and downregulated the mRNA expression of IFN-β, IRF7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In mammals, RNF135, TRIM14, 25, and 65 bind helicases involved in immune signaling using their PRY-SPRY domains, while the function of TRIM47 is unknown ( 104 ). Duck TRIM29 inhibits signaling pathways downstream of these helicases by catalyzing the addition of K29-linked ubiquitin to the signaling adaptor MAVS, resulting in a decrease in IFN signaling downstream of MAVS ( 50 ). RNF135 has previously been excluded from TRIM repertoires because it does not have the classical RBCC motif, as it is missing the B-box domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, RNF135, TRIM14, 25, and 65 bind helicases involved in immune signaling using their PRY-SPRY domains, while the function of TRIM47 is unknown ( 104 ). Duck TRIM29 inhibits signaling pathways downstream of these helicases by catalyzing the addition of K29-linked ubiquitin to the signaling adaptor MAVS, resulting in a decrease in IFN signaling downstream of MAVS ( 50 ). RNF135 has previously been excluded from TRIM repertoires because it does not have the classical RBCC motif, as it is missing the B-box domain.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals and ducks, TRIM25 catalyzes the addition of polyubiquitin for the activation of retinoic-acid-inducible gene I (RIG-I) in antiviral signaling ( 46 , 49 ). Duck TRIM29 was identified as a negative regulator of the RIG-I signaling pathway ( 50 ). A gene described as TRIM39 in chicken is predominantly expressed in the spleen, but has not yet been functionally characterized ( 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional research revealed that PA151R and TBK1 engage in a competitive interaction with the E3 enzyme TNF receptor-related protein TRAF6, leading to the suppression of TRAF6 expression via the apoptosis pathway. This ultimately results in the inhibition of TBK1 phosphorylation and the suppression of ASFV replication [113]. PA151R negatively regulates IFN-I production.…”
Section: 3mentioning
confidence: 99%
“…In fungi, ncRNAs, such as lncRNA and micro-RNA-like (milRNA) molecules are involved in cell division, nutrient perception, sexual reproduction, and other processes [13][14][15]. CircRNAs regulate gene expression in diverse biological processes in Ganoderma lucidum [16], while milRNAs can regulate P. cornucopiae fruiting body development [17]; however, there are no reports of investigation of the regulation of fruiting body color by ncRNAs.…”
Section: Introductionmentioning
confidence: 99%